Analysis of the Relevance of Class XI SKI Teaching Materials Based on Bloom's Taxonomy Approach - Farandika Nanda Pratama (Journal of Insan Mulia Education, 2024)
This research aims to analyze the SKI teaching materials for grade XI, even in the semester published by KEMENAG, especially in terms of the clarity of the material content and its relevance using Bloom's taxonomy analysis, covering students' cognitive, affective, psychomotor, and psychological domains. The researcher used library research through reading, reviewing, and analyzing several available literature, including books, notes, and reports of previous research results. The research technique uses descriptive analysis based on the collection of available sources. The study began by selecting Chapter 2 on Islamic Civilization During the Ottoman Empire from the teaching materials relevant to the 2019 Curriculum. This material was analyzed using Bloom's Taxonomy to evaluate the scope of the cognitive, affective, and psychomotor domains. The data that has been collected will then be analyzed descriptively to identify relevant findings. The results of this study state that the teaching materials for Islamic Cultural History for grade XI semester I have presented subject matter that is by the revised Bloom's Taxonomy based on the cognitive, affective, psychomotor domains and student development. Although there are still some weaknesses, it can be said that the material is relevant to the Revised Bloom's Taxonomy, which also meets the criteria of KI and KD. This teaching material is expected to be a student's reference book when studying. Thus, educators are expected to be able to deliver the material using various methods so that students can easily understand and not get bored so that learning objectives can be achieved to improve the quality of education.